Faktor- Faktor Yang Mempengaruhi Tingkat Penyerapan Anggaran Belanja Satker Pusat Di Daerah Lingkup Kemenlhk - Dwi Perwita Sari Sutono; Novita Weningtyas Respati; Lili Safrida (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2022)
This study examined and analyzed the effect of budget planning, budget execution, internal supervision, and regulation on the level of absorption of the budget for the central working unit within the scope of the Ministry of Environment and Forestry spread over Indonesia. The primary data were derived from questionnaires to answer questions from 193 respondents. The sample selection used was the Slovin formula. The data were analyzed using a multiple linear regression analysis technique through the SPSS 26 program. Partial test results show that budget planning, budget execution, and regulations significantly affect the level of budget absorption.